FAKTOR RISIKO KOMPLIKASI KRONIS (KAKI DIABETIK) DALAM DIABETES MELLITUS TIPE 2 - Lina Ema Purwanti; Sholihatul Maghfirah (The Indonesian Journal of Health Science, 2017)
Diabetes Mellitus (DM) is a chronic disease characterized by blood glucose levels than normal and impaired metabolism of carbohydrates, fats and proteins caused by insulin deficiency relative or absolute. Chronic complications that often occur in patients with Type 2 diabetes mellitus is diabetic foot. The purposed of this study was to analyzed the risk factors of chronic complications (diabetic foot) in patients with Type 2 diabetes mellitus. The design of this research was descriptive analytic with cross sectional approach. This study will be conducted in the Medical Practitioners Prolanis of Ponorogo to 75 patients with Type 2 diabetes mellitus using questionnaire and observation. The result showed that only a visual impairment factors that significantly influence the incidence of diabetic foot, with p value (Chi Square) 0.119, and OR: 4. Knowing the risk factors that most influence on the incidence of chronic complications (diabetic foot) in patients with Type 2 diabetes can be a non-pharmacological preventive measures that can prevent diabetic foot are at risk of disability due to amputation and death.